Pico hydro generation system for building’s supplementary energy - Kamarul ‘Asyikin Mustafa; Murniati Syaripuddin; Norlaili Ismaila; Nazrul Fariq Makmor; Mohamad Fakri Ishak (Penerbit Universiti Kebangsaan Malaysia, 2021)
Renewable energy is an important source in supplying energy to the masses as it is sustainable, environmentally friendly, and require less maintenance cost compared to the conventional fossil fuel resources. This paper describes the study of a pico hydro generation system. The power generation system uses water utilized by a building as the source to generate energy. In the study, the system prototype is designed using several combinations of piping system where different sizes, shapes, and turbine positions are used. The energy from the water flowing through the piping system will be converted into electrical energy through the turbine system that is placed in the main water tank. The best combination of pipeline system for the prototype is by using two different positions of water jet. This combination requires lower water pressure and is able to generate 198 W of energy.